Propeptide glycosylation and galectin‐3 binding decrease proteolytic activation of human proMMP‐9/progelatinase B. (30th November 2018) - Boon, Lise; Ugarte‐Berzal, Estefania; Martens, Erik; Vandooren, Jennifer; Rybakin, Vasily; Colau, Didier; Gordon‐Alonso, Monica; van der Bruggen, Pierre; Stöcker, Walter; Becker‐Pauly, Christoph; Witters, Peter; Morava, Eva; et al.
Abstract : Matrix metalloproteinases (MMPs) are secreted as proenzymes, containing propeptides that interact with the catalytic zinc, thereby controlling MMP activation. The MMP‐9 propeptide is unique in the MMP family because of its post‐translational modification with an N‐linked oligosaccharide. ProMMP‐9 activation by MMP‐3 occurs stepwise by cleavage of the propeptide in an aminoterminal (pro‐AT) and carboxyterminal (pro‐CT) peptide. We chemically synthesized aglycosyl pro‐AT and pro‐CT and purified recombinant glycosylated pro‐AT S f−9 . First, we report new cleavage sites in the MMP‐9 propeptide by MMP‐3 and neutrophil elastase. Additionally, we demonstrated with the use of western blot analysis a higher resistance of glycosylated versus aglycosyl pro‐AT against proteolysis by MMP‐3, MMP‐9, meprin α, neutrophil elastase and by protease‐rich synovial fluids from rheumatoid arthritis patients. Moreover, we investigated the effect of glycosylation on proteolytic activation of human proMMP‐9 with the use of zymography and dye‐quenched gelatin cleavage analysis. Compared to recombinant Sf‐9 proMMP‐9 glycoforms, larger oligosaccharides of human neutrophil proMMP‐9 increased resistance against proteolytic activation. Additionally, proMMP‐9 from Congenital Disorder of Glycosylation patients, compared to healthy controls, showed a higher activation rate by MMP‐3. Finally, we demonstrated that glycan‐galectin‐3 interactions reduced proMMP‐9 activation. In conclusion, modification of MMP‐9 propeptide glycosylation is a fine‐tuning mechanism and co‐determines the specific activity of MMP‐9 in physiology and pathology. Enzymes: MMP‐9EC 3.4.24.35, MMP‐3EC 3.4.24.17, meprin αEC 3.4.24.18, neutrophil elastaseEC 3.4.21.37, trypsinEC 3.4.21.4 and PNGase FEC 3.5.1.52 . Abstract : Matrix metalloproteinases (MMPs) contain propeptides that interact with the catalytic zinc, thereby controlling MMP activation. The MMP‐9 propeptide (green) is unique within the MMP family having an N‐linked oligosaccharide (purple). We showed that MMP‐9 propeptide glycosylation itself and galectin‐3 (pink) binding are fine‐tuning mechanisms of the proteolytic activation process, by MMP‐3 (cyan), thereby co‐determining the specific activity of MMP‐9.